Ultra-Compact Slitted Flower-Shaped Dual-Band Monopole Antenna for Modern Portable Devices - Jeremiah O Abolade; Dominic B. O. Konditi (International Journal of Antennas and Propagation)
A meanderingly slitted bio-inspired (MSB)-shaped antenna is presented in this work. The footprint of the proposed MSB antenna is 12 × 10 mm20.12×0.10λg2  at  2.1GHz. The MSB antenna proposed in this operates at 2.1 GHz and 5.2 GHz frequencies with a bandwidth of 70 MHz and 570 MHz and a radiation efficiency of 52.5% and 96%, respectively, which is suitable for UMTS, radio navigation, Long Term Evolution (LTE), and 5 GHz Wireless Local Area Network (WLAN) applications. The proposed MSB antenna demonstrates a peak gain of 2.9 dBi at 5.2 GHz and an omnidirectional radiation pattern at both E-plane and H-plane in both operating bands. The fabrication and measurement of the proposed antenna prototype are presented. The parametric study of the proposed structure is performed and presented. Therefore, the proposed antenna is a promising candidate for modern portable devices.